Coiled Rings of DNA Released from Cells Infected with Bacteriophages T7 or T4 or from Uninfected Escherichia coli - Bernstein, Carol (1974)
The replicating intracellular DNA of phage T7 was labeled at high specific activity with tritiated thymidine. The DNA of uninfected Escherichia coli was similarly labeled. Portions of cells which contained replicating phage T7 or E. coli DNA were lysed by a lysozyme, freeze-thaw, sodium lauryl sulfate procedure, and the DNA was spread on Millipore membranes for visualization by autoradiography. The DNA of phage T7 appeared to be highly concatenated reaching lengths of up to 721 μm. Much of the DNA of phage T7 and E. coli was retained in compact globular structures. In addition, orderly coiled rings of varying diameter up to about 43 μm were regularly observed. Similar coiled ring structures were also observed in autoradiographs of replicating phage T4 DNA which had been prepared in previous experiments. Worcel and Burgi (27) have presented evidence that E. coli chromosomes, when gently extracted from cells, are in a multilooped and superhelically twisted configuration. The coiled rings which we have observed may correspond to the relaxed, multilooped configurations which they find when the superhelical twists have been relieved by one or more nicks in each loop.